Novel Long‐Acting GLP‐2 Analogue, FE 203799 (Apraglutide), Enhances Adaptation and Linear Intestinal Growth in a Neonatal Piglet Model of Short Bowel Syndrome with Total Resection of the Ileum. Issue 7 (6th January 2019) - Slim, George M.; Lansing, Marihan; Wizzard, Pamela; Nation, Patrick N.; Wheeler, Sarah E.; Brubaker, Patricia L.; Jeppesen, Palle B.; Wales, Paul W.; Turner, Justine M.
Abstract: Background: Glucagon‐like peptide‐2 (GLP‐2) is an intestinotrophic factor released from L‐cells in the ileum, a segment commonly resected or atretic in neonatal short bowel syndrome (SBS). In piglets, ileal resection decreases intestinal adaptation and endogenous GLP‐2 production, whereas exogenous replacement promotes adaptation. In this study, we determined the effect of a novel long‐acting GLP‐2 analogue, FE 203799 (FE; apraglutide), upon intestinal growth, adaptation, and function in neonatal SBS piglets without ileum. Methods: Neonatal piglets were randomized to saline (n = 10) vs FE treatment (n = 8). All piglets underwent 75% intestinal resection with jejunocolic anastomosis and were pair‐fed parenteral and enteral nutrition. Saline and FE (5 mg/kg) treatments were administered subcutaneously on days 0 and 4. On day 6, 24‐hour fecal samples were collected for subsequent nutrient analysis. On day 7, small‐intestinal length and weight were measured and tissue collected for analyses. Results: On day 7, saline and FE‐treated piglets were healthy and gained equivalent weight ( P = 0.12). Compared with saline piglets, FE‐treated piglets had lower fecal fat ( P = 0.043) and energy ( P = 0.043) losses and exhibited intestinal lengthening ( P = 0.001), greater small‐intestinal weight ( P = 0.004), longer villus height ( P = 0.027), and greater crypt depth ( P = 0.054). Conclusions: The subcutaneous GLP‐2 analogue, FE, enhanced intestinal adaptation in a neonatal model of SBS without ileum. The observed intestinal lengthening with FE treatment was unique compared with our prior experience with native GLP‐2 in this same model and has important clinical implications for treating neonatal SBS. At this developmental stage, growth in the intestine, if augmented, could accelerate weaning from parenteral nutrition.